Characterization of Alginate Lyase from Pseudomonas syringae pv. syringae - Preston, Lori A. (American Society for Microbiology, 2000)
The gene encoding alginate lyase (algL) in Pseudomonas syringae pv. syringae was cloned, sequenced, and overexpressed in Escherichia coli. Alginate lyase activity was optimal when the pH was 7.0 and when assays were conducted at 42°C in the presence of 0.2 M NaCl. In substrate specificity studies, AlgL from P. syringae showed a preference for deacetylated polymannuronic acid. Sequence alignment with other alginate lyases revealed conserved regions within AlgL likely to be important for the structure and/or function of the enzyme. Site-directed mutagenesis of histidine and tryptophan residues at positions 204 and 207, respectively, indicated that these amino acids are critical for lyase activity.